The Impact of the Application of Make-a Match Technique Towards Students’ Vocabulary Mastery - Dewi Maduratna (International Conference on Education and Language (ICEL), 2014)
The purpose of this research were to find out the impact of the application of Make-a Match technique towards students’ vocabulary mastery of grade seven of SMP Tri Sukses Natar South Lampung. This research was using an experimental method in the quantitative form by collecting data from documentation, and test. The sample of the research was 25 students of seven grade. The data were collected by using two pre-tests and two post-tests in control group and experimental group. Statistical formula t-Test two group design was utilized to analyze data. The result showed statistically significsnt in the critical value at probability level of 5% is 2,01 and at probability 1% is 2,68 as t-value is 7,41, therefore p value is smaller than t value ( 2,01 < 2,68 < 7, 41). So, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. it can be concluded that using Make-a Match technique in teaching vocabulary is quite success. It is not only effective to lead students feel more interesting and enjoy doing activity in the class, but also it can give the students the opportunities to be active in learning English vocabulary.